Gallstone Ileus: A Stone In The Way (Journal of Society of Surgeons of Nepal, 2023)
Gallstone ileus, a rare complication of cholelithiasis, is caused by an impaction of gallstones within the gastrointestinal tract leading to mechanical intestinal obstruction. Here in, we describe a case of gallstone ileus in a 62-year-old woman successfully treated with enterolithotomy. The patient was discharged home after an uneventful post-operative period. Gallstone ileus is an uncommon complication of gallstones and a rare cause of intestinal obstruction, with often delayed presentation and non-specific symptoms. The preferred approach is enterolithotomy. Elective cholecystectomy after the acute episode is controversial.